Surface modification of TiO2 nanoparticles with silane coupling agent for nanocomposite with poly(butyl acrylate). (14th May 2015) - Xiang, B.; Jiang, G.; Zhang, J.
<x content-type="archive" xml:space="preserve">Abstract</x> In order to enhance the compatibility of TiO2 nanoparticles in poly(butyl acrylate) (PBA) matrix, surface modification of TiO2 was conducted using 3-methacryloxypropyl-trimethoxysilane (MPS). To improve the effect of surface modification, TiO2 was predispersed in ethanol via ultrasonic waves. The process was investigated in detail to obtain the optimum condition of ultrasonic dispersion. The dispersion of TiO2 in ethanol was evaluated via sedimentation rate. Fourier transform infrared spectroscopy and thermogravimetric analysis were performed to investigate the effect of surface modification. It was found that the organic functional groups of MPS had been successfully grafted onto the surface of TiO2 nanoparticles. Finally, both neat PBA film and TiO2/PBA composite film were prepared and characterised. The modified TiO2 presented good compatibility in PBA matrix.